Application Design of Human Resource Information System on Binus Student Learning Community of Bina Nusantara University - Eileen Heriyanni; Aswin Wibisurya; Timothy Yudi Adinugroho (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Information exchange between human resources within an organization is a valuable asset that must be managed properly. Information technology now supports information management between human resources through Human Resource Information System (HRIS). Binus Student Learning Community (BSLC) implementsdifferent technologies for each work they performed so that affect the quality of information exchange and performance of their members. This study aims to streamline the used technology in BSLC by combining it all into the same system through the implementation of HRIS constructed by Extreme Programming (XP) method. Results of this research is the web-based HRIS BSLC application and expected to improve the quality of information exchange and optimize the performance of BSLC’s members.